Determinants and impacts of individual and combined adoption of sustainable agricultural practices in Uzbekistan - Nodir Djanibekov; Zafar Kurbanov; Abdusame Tadjiev; Boubaker Dhehibi; Akmal Akramkhanov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2026)
Agricultural sector in Uzbekistan is undergoing rapid modernization driven by institutional reforms and mounting pressure to ensure sustainable land and water resource use. This study investigates the adoption and impacts of four sustainable agricultural practices (SAPs) promoted for sustainable intensification: crop rotation, manure application, drip irrigation, and laser levelling. Using nationally representative survey data from 1,225 farms across four major regions (Andijan, Kashkadarya, Khorezm, and Samarkand) collected in 2024, we employ a multivariate probit model to analyze complex, inter-dependent adoption decisions and their determinants. Subsequently, we apply treatment-effects models to assess the impact of individual practices and selected bundles on three critical outcomes: farm revenue, an agronomic sustainability index, and the gender wage gap among seasonal workers. Our analysis reveals that SAP adoption patterns are highly practice-specific. Crucially, perceived profitability, benefits and challenges are strong predictors of uptake, while standard structural variables (education, farm size, and extension contact) are inconsistent determinants across practices. Modern technologies are more strongly linked to institutional arrangements, farm structure, and training than are traditional practices. Results on impact are nuanced: no single technology improves all three outcomes simultaneously. Drip irrigation emerges as the most promising individual practice, significantly raising both revenue and sustainability. In contrast, laser levelling shows no clear average economic gains. Importantly, SAP bundles consistently outperform single practices on sustainability and sometimes on revenue. Social impacts are mixed: crop rotation tends to widen, while the joint adoption of laser levelling and drip irrigation narrows, the gender wage gap. Overall, the findings underscore the necessity of practice-specific and portfolio-based policy support for sustainable agriculture in reforming transition economies.
urn:nbn:de:gbv:3:2-123456789-1175832
Keywords: 330; Technology adoption; Irrigated farming systems; Multivariate probit; Treatment effects analysis